A Robust Constant–Voltage DC Triboelectric Nanogenerator Using the Ternary Dielectric Triboelectrification Effect. Issue 2 (22nd November 2022) - Li, Qianying; Hu, Yawen; Yang, Qianxi; Li, Xiaochuan; Zhang, Xuemei; Yang, Huake; Ji, Peiyuan; Xi, Yi; Wang, Zhong Lin
Abstract: Nowadays, the development of direct current triboelectric nanogenerators (DC‐TENGs) is oriented toward practical applications such as real‐time efficient harvesting and supplying energy. This demands DC‐TENGs with a low loss factor, high energy utilization efficiency, device portability, and output stability. Herein, a constant‐voltage DC‐TENG (C‐DC‐TENG) with robust output performance, using the ternary dielectric triboelectrification effect is demonstrated, which gives a crest factor of 1.0082. The key to improving the output charge density is the number of subdivision units, a result of theoretical simulations and experiments of C‐DC‐TENG. The optimized C‐DC‐TENG achieves not only an output charge density of 3.902 mC m −2 per round but also an average power density of 8.77 W m −2 (3.508 W m −2 Hz −1 ), which both set a new record for the rotary DC‐TENG. Moreover, introducing soft polyester fur enables C‐DC‐TENG to maintain 100% output without wear after 800 000 cycles. This C‐DC‐TENG is faultlessly competent for powering 2784 LEDs in series and 25 parallel‐connected hygrothermographs continuously. This work provides a promising technique for large‐scale clean energy harvesting, accelerating the progress toward practical applications of DC‐TENG. Abstract : A constant‐voltage DC‐triboelectric nanogenerator (C‐DC‐TENG) is constructed based on the ternary dielectric triboelectrification effect, achieving high average power density, high output charge density, high stability, and low crest factor (1.0082), and its superior and sustained output properties are expected to greatly accelerate the process of utilizing TENG for large‐scale energy harvesting.